1980
DOI: 10.2527/jas1980.513679x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Regulation of Luteinizing Hormone and Follicle Stimulating Hormone Secretion in Young Male Lambs1

Abstract: SummaryPolydimethylsiloxane (Silastic) capsules containing crystalline testosterone were implanted subcutaneously in castrate lambs and evaluated for their ability to (1) provide stable, physiological concentrations of serum testosterone and (2) regulate secretion of LH and FSH. Testosterone was nondectable (<.2 ng/ml) between 12 and 24 weeks of age in the serum of castrate lambs implanted with empty capsules but was increased at those ages in Iambs implanted with 20 cm (1.2 + .1 and .5 +-.1 ng/ml), 60 cm (2.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…Presumably LH and FSH levels decline after their initial peak in the young ram due to the establishment of negative feedback by substances of gonadal origin. It is known that both T and DHT can exert potent negative feedback effects on LH and FSH secretion in the ram (Schanbacher 1980;D'Occhio et al 1983), but a role for D and the 5cr-reduced androgens measured in the present study awaits investigation. The pattern of serum androgen concentrations noted in the present study in comparison to the values found in wether serum would suggest that the ovine interstitial cell can produce all six androgens, as has been suggested for the rat (Podesta and Rivarola 1974).…”
mentioning
confidence: 59%
“…Presumably LH and FSH levels decline after their initial peak in the young ram due to the establishment of negative feedback by substances of gonadal origin. It is known that both T and DHT can exert potent negative feedback effects on LH and FSH secretion in the ram (Schanbacher 1980;D'Occhio et al 1983), but a role for D and the 5cr-reduced androgens measured in the present study awaits investigation. The pattern of serum androgen concentrations noted in the present study in comparison to the values found in wether serum would suggest that the ovine interstitial cell can produce all six androgens, as has been suggested for the rat (Podesta and Rivarola 1974).…”
mentioning
confidence: 59%
“…El aumento temprano y luego sostenido de la concentración de LH hasta la semana 12 resulta de una disminución en la sensibilidad del eje hipotálamo-hipófisis a la retroalimentación negativa de los esteroides, que representa tal vez el inicio del proceso puberal (14) . El subsiguiente descenso de los parámetros de los perfiles de LH después de la semana 12 (Estudio 1) y de la respuesta a GnRH después de la semana 16 (Estudio 2), en conjunto con el aumento de las concentraciones de T, pudieron ser consecuencia del establecimiento de los mecanismos de retroalimentación negativa de los esteroides gonadales (2,23) .…”
Section: Discussionunclassified
“…The early and then sustained increase in LH concentration until wk 12 results from a decrease in the sensitivity of the hypothalamus-hypophysis axis to steroid negative feedback, representing perhaps the beginning of the pubertal process (14) . The subsequent decline in the LH profile parameters after wk 12 (Study 1) and in the response to GnRH after wk 16 (Study 2), in conjunction with increasing T values, were probably consequence of the establishment of the mechanisms of negative feedback of gonadal steroids (2,23) .…”
Section: Discussionmentioning
confidence: 99%
“…The rapid rise in plasma concentrations of the gonadotropins LH and FSH after castration of rams [1][2][3][4][5][6][7] indicates that secretion of the gonadotropins is under the negative feedback control of testicular hormones. While control of FSH and LH secretion by the negative feedback of testicular steroids has been studied extensively in rams, the importance of the testicular glycoprotein hormone inhibin as a feedback regulator is less well understood.…”
Section: Introductionmentioning
confidence: 98%
“…While control of FSH and LH secretion by the negative feedback of testicular steroids has been studied extensively in rams, the importance of the testicular glycoprotein hormone inhibin as a feedback regulator is less well understood. Many studies have shown that both androgens and estrogens negatively regulate the secretion of FSH and LH [1][2][3][4][5][6][8][9][10][11][12][13][14][15], although the doses of testicular steroids used have not always been in the physiological range. When a physiological dose of testosterone was administered to castrated rams for 7 days, the plasma concentrations of LH were reduced into the range of values found in intact rams but there was no significant reduction of plasma concentrations of FSH [16].…”
Section: Introductionmentioning
confidence: 99%